PENGARUH LINGKUNGAN SOSIAL PADA KEPUTUSAN REMAJA UNTUK MEROKO MEREK MALBORO (Studi Kasus Pada Siswa SMA di Kota Ternate) - Ibnu Sina Hi Yusuf (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2013)
Cigarette is one of the unique product (especially the way consumption) because these products give satisfaction to the consumer through the smoke. This result measure on influence of variable X1 teenagers to smoke. By using Multiple Regression Method, the results show that this variable X1 (Friend), X2 (Parents) and X3 (idol Figure) are significant and influential of the variable Y (The Smoking Decision).